Enhanced infrared sensing properties of vanadium pentoxide nanofibers for bolometer application. (July 2018) - Vadnala, Sudharshan; Paul, Nirupam; Agrawal, Amit; Singh, S.G.
Abstract: The main aim of this work is to report an alternative technique of creating vanadium pentoxide (V2 O5 ) based uncooled infrared (IR) detector, by a state-of-the-art V2 O5 nanofibers, manufactured by facile and economical electrospinning process. The nanofibers were thermally and electrically characterized to determine their bolometric performance. The nanofibers show maximum voltage responsivity ( R v ) 6987.3 V/W at 100 mA DC bias, in a normal room temperature and pressure condition. Nanofibers show very good thermal response ( τ s ) and recovery time ( τ r ) when subjected to a periodic On-Off cycle of IR lamp (150 W) illumination. Temperature dependent resistance measurement shows that nanofibers are exhibiting semiconductor to metallic phase transition at 67 °C with maximum temperature coefficient of resistance (TCR%) − 1.6%/K at the transition. V2 O5 nanofibers characterized using X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and Raman Spectroscopy confirms their crystallinity and elemental composition. The optical band gap of the nanofibers is analyzed by UV–Visible spectroscopy. Scanning electron microscopy (SEM) and atomic force microscopy (AFM) images confirms their microstructural dimensions and surface homogeneity. The entire analysis reaffirms the suitability of V2 O5 nanofibers as one of the futuristic sensing material for IR imaging applications.